ANALISIS PENGARUH KEMANDIRIAN KEUANGAN DAERAH PADA KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Periansya Periansya (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2019)
This research was conducted with the aim to know the regional wealth, revenue sharing fund and general allocation fund to the independence of regional finance at the Government of Regency/City in South Sumatra Province. This research was conducted in the period 2014 until 2017. The population in this study is all of Regency/City in the Province of South Sumatra. Sample determination is determined by the Purposive sampling technique as many as 11 regencies/cities in South Sumatera Province. The type of research is quantitative research with secondary data. Form the Budget Realization from the Audit Result Report (LHP) BPK RI 2014 – 2017. The analytical method used is multiple linear regression analysis with panel data. The results showed that the regional wealth and general allocation fund partially influenced the direction of a positive relationship to regional financial independence. While revenue sharing funds partially did not influence regional financial independence. In addition simultaneously regional wealth, revenue sharing funds and general allocation funds simultaneously have a significant effect on regional financial independence at the government of regency/city in South Sumatra Province